The virtue of teaching and learning natural sciences in postmodern times: a reflexive approach - Lara Calderón, Pablo Lleral (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The agricultural sector was prepared to adopt foreign agrochemicals based on supply, which apparently revolutionized the agricultural activity, for a better quality of life. The objectives are based on the following: review the documentary sources to know the current episteme of agroecology, classify the information in sections, build the discourse based on the object of study, analyze the documentary results. The research is qualitative, the methodology is documentary based on the review of periodic sources inherent to agroecology in the context of Bucaramanga, Department of Santander, in Colombia.